Interpreting Article 22(2) of the 1945 Constitution of the Republic of Indonesia Post Constitutional Court Decision 54/PUU-XXI/2023 - Riqiey, Baharuddin; Huda, Muhammad Ahsanul (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2024)
The aim of this research is to elucidate the interpretation of Article 22, paragraph (2) of the 1945 Constitution of the Republic of Indonesia, particularly focusing on the phrases "obtain approval from the House of Representatives" and "in the following trial." Employing a normative legal research approach, the study utilizes a statutory regulatory approach, a conceptual approach, and a case approach. The legal materials encompass both primary and secondary legal sources. The research findings delineate that the phrase "obtain approval from the People's Representative Council" in Article 22, paragraph (2) of the 1945 Constitution of the Republic of Indonesia signifies: (i) the requirement for the President to submit the Perppu to the DPR for approval; and (ii) the discretion of the DPR to either approve or disapprove the Perppu. Meanwhile, the interpretation of the phrase "in the following trial" entails: (i) the period during which the Perppu is submitted to the DPR by the President; (ii) the initial session of the DPR following the submission of the Perppu; and (iii) the initial session period after the expiration of the maximum time limit for the President to submit the Perppu to the DPR.